1999
DOI: 10.2466/pms.1999.88.2.541
|View full text |Cite
|
Sign up to set email alerts
|

Body-Size Estimations in Children Six through Fourteen: A Longitudinal Study

Abstract: Estimates of perceived and ideal body size were collected in 216 boys and girls ages 6 through 14 years. Video methodology was used to adjust the width of a life-size frontal image of the children. Longitudinal data were collected annually for three years, beginning at ages 6, 9, and 12. Three psychological methods were used, including the method of adjustment, staircase method, and adaptive probit estimation technique which permitted separate measures of the children's point of subjective equality and just no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 21 publications
2
7
0
1
Order By: Relevance
“…For instance, children tend to overestimate body width and underestimate body length, with a sharp drop in overestimation between ages 10 and 11 and a more gradual decline at later ages (Halmi, Goldberg, & Cunningham, 1977), at the tinle when adolescents' heightened sell-consciousness becomes evident (Peterson & Roscoe, 1991). A more recent study using video methodology to evaluate self-perception of body width showed a fairly accurate self-estimation even in children as young as six years of age and confirmed a decrease in overestimation with age (Gardner, Friedman, Stark, & Jackson, 1999).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…For instance, children tend to overestimate body width and underestimate body length, with a sharp drop in overestimation between ages 10 and 11 and a more gradual decline at later ages (Halmi, Goldberg, & Cunningham, 1977), at the tinle when adolescents' heightened sell-consciousness becomes evident (Peterson & Roscoe, 1991). A more recent study using video methodology to evaluate self-perception of body width showed a fairly accurate self-estimation even in children as young as six years of age and confirmed a decrease in overestimation with age (Gardner, Friedman, Stark, & Jackson, 1999).…”
mentioning
confidence: 83%
“…"Body dissatisfaction" has been shown to be strongly related to the frequency of reading fashion magazines (Field, Cheung, Wblf, Herzog, Gortmaker, & Colditz, 1999). Girls' body image shows critical changes during adolescence (Tadai, Kanai, Nakamura, & Nakejima, 1994), and a rise in "body dissatisfaction" has been shown for girls at the age of nine years (Gardner, et a/., 1999). It has been suggested that the current cultural preference for the thin, prepubescent female physique primes adolescent girls to be increasingly &satisfied with their bodes as they mature (Siegel, Yancey, Aneshensel, & Schuler, 1999).…”
mentioning
confidence: 96%
“…Standard conservation tasks reveal that children at these ages have great difficulty simultaneously considering more than one size dimension of a figure, and often focus on height rather than width (Piaget, 1977). Likewise, seeing only one figure at a time (rather than a number presented simultaneously as in an array) may increase accuracy; children have performed better when discrete, versus comparative, judgements were required (Gardner, Friedman, Stark, & Jackson, 1999). Creative alternatives to the array have shown promise with adults (Gardner & Brown, 2010), but have not yet been tested with children.…”
Section: Self-recognitionmentioning
confidence: 97%
“…Gardner, Friedman, Stark, et al (1999) asked children aged 7-13 years to select from an eight-figure array which figure 'most boys/girls looked like'; both boys and girls rated girls' size as smaller than boys' size, even though children do not actually differ in size at this age. This suggests that either they internalised (inaccurate) societal messages about children's body size, or they are generalising from the real body size discrepancy of adults .…”
Section: Representational Abilitiesmentioning
confidence: 99%
“…A 3-year longitudinal study in our laboratory [88] using a video distortion methodology measured BSE in 3 groups of children between the ages of 6-8, 9-11, and 12-14. Children slightly overestimated their body size at age 6 by about 5% with accuracy steadily increasing through age 14, at which time they were very accurate. There were no gender differences.…”
Section: Agementioning
confidence: 99%